2013
DOI: 10.1167/13.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Statistical learning in the past modulates contextual cueing in the future

Abstract: Observers' capability to extract statistical regularities from the visual world can facilitate attentional orienting. For instance, visual search benefits from the repetition of target locations by means of probability learning. Furthermore, repeated (old) contexts of nontargets contribute to faster visual search in comparison to random (new) arrangements of nontargets. Chun and Jiang (1998) called this effect "contextual cueing" because old contexts provide spatial cues to repeated target locations. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…In our study, some learning occurred in the semantically incongruent condition. This is similar to the effect Zellin et al (2013) found in a contextual cueing task, in which subjects maintained different sets of predictions for target locations depending on the surrounding context.…”
Section: Comparison To Prior Worksupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, some learning occurred in the semantically incongruent condition. This is similar to the effect Zellin et al (2013) found in a contextual cueing task, in which subjects maintained different sets of predictions for target locations depending on the surrounding context.…”
Section: Comparison To Prior Worksupporting
confidence: 81%
“…Learning has been reported in search tasks using abstract displays, where the statistics of target locations in relation to a surrounding context are learned quickly, and are retained in long-term memory (Chun & Jiang, 1998;Chun, 2000;Chun & Jiang, 2003). Learning the relationship between a target and the surrounding context depends on the predictability of the relationship Zellin et al, 2013). In our study, some learning occurred in the semantically incongruent condition.…”
Section: Comparison To Prior Workmentioning
confidence: 50%
“…The sample size was determined on the basis of previous comparable studies (e.g., Assumpção, Shi, Zang, Müller, & Geyer, 2015 ; Geringswald, Herbik, Hofmüller, Hoffmann, & Pollmann, 2015 ; Geyer et al, 2010 ; Zellin et al, 2011 ; Zellin et al, 2013a ; Zellin von Mühlenen, Müller, & Conci, 2013b ; Zellin von Mühlenen, Müller, & Conci, 2014 ; Zinchenko et al, 2018 ), which typically tested around 14 (or fewer) participants. Sample size estimation was informed by previous contextual-cueing studies using a training-phase/test-phase design (e.g., Assumpção et al, 2015 ; Geringswald et al, 2015 ; Zellin, von Mühlenen, et al, 2013b ; Zellin et al, 2014 ; Zinchenko et al, 2019 ). On the basis of the number of participants tested in and statistical measures provided by these studies, a sample size of 12 to 14 participants suffices to detect a lack-of-adaptation effect with a power of 0.8 in a single experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The original study of this paradigm (Chun & Jiang, 1998) preselected target locations for random contexts. Thus, participants could have learned repeated target locations (Zellin, von Mühlenen, Müller, & Conci, 2013) and attended selectively to a subset of possible target locations when the context is unfamiliar to them. The present design excluded this form of learning with random contexts.…”
Section: Methodsmentioning
confidence: 99%